Health facilities' capability to provide comprehensive postabortion care in Sub‐Saharan Africa: Evidence from a cross‐sectional survey across 210 high‐volume facilities. (21st January 2022) - Compaoré, Rachidatou; Mehrtash, Hedieh; Calvert, Clara; Qureshi, Zahida; Bello, Folasade Adenike; Baguiya, Adama; Msusa, Ausbert Thoko; Idi, Nafiou; Govule, Philip; Tunçalp, Ӧzge; Kouanda, Seni
Abstract: Objective: To evaluate the capability of high‐volume comprehensive emergency obstetric care (CEmOC) health facilities on the provision of comprehensive postabortion care (PAC) in Sub‐Saharan Africa and to determine the frequency of women with severe abortion‐related complications in high capability facilities. Methods: A cross‐sectional analysis conducted across 11 countries in Sub‐Saharan Africa, using facility‐level information from the World Health Organization (WHO) Multi‐Country Survey on Abortion‐related morbidity (MCS‐A) between 2017 and 2018. PAC signal functions were adapted to assess facilities' capability to deliver comprehensive PAC through infrastructure, standard comprehensive capability, and extended comprehensive capability to provide PAC. The percentage of facilities with each signal function and distribution of facilities by number of signal functions were calculated for the three capability categories. Distribution of severe abortion complications by facility capability score was assessed. Results: Of 210 high‐volume CEmOC facilities included, 47.9% ( n  = 100) had capability to provide all facility infrastructure signal functions, 54.4% ( n  = 105) for standard comprehensive PAC, reducing to 17.7% ( n  = 34) for extended comprehensive PAC capability. Overall, there were gaps in extended capabilities including availability of a functioning ICU (available in 37.3% of facilities) and providers 24/7 (65.5% of facilities reported an obstetrician available 24/7 dropping to 41.3% for anesthesiologists). Facilities' PAC capability varied across regions. Overall, 34.6% ( n  = 614) of women with severe abortion‐related complications were treated in facilities with the maximum capability score for extended comprehensive PAC. Conclusion: Although high levels of capability to provide abortion‐related care for most signal functions were evident, significant gaps that impact on the management of severe abortion‐related complications remain, particularly related to extended facility capabilities including specialized human resources and ICU. Synopsis: Although levels of availability of key resources to manage abortion‐related complications were high, important resources for the most severe abortion‐related complications were not readily available, notably specialized human resources and ICU.